Interwar Literary Criticism. An Unknow Letter from Melchior Wańkowicz to Alfred Jesionowski - Płaszczewska, Olga (Porównania, 2025)
The main purpose of the essay is to reflect on the relationship of the critic Alfred Jesionowski with the “Rój” publishing house and its founder, Melchior Wańkowicz, as a writer. First, Jesionowski’s views and opinions on books published by “Rój” in the 1930s are presented briefly along his thoughts on the role of both an editor and a reviewer. Then it focuses on Wańkowicz’s letter to Jesionowski from October 7, 1936, concerning the reportage Na tropach Smętka (On Smętek’s Trail) and giving some interpretative hints which were used in Jesionowski’s later reviews. Finally, Wańkowicz’s two dedications to Jesionowski are analysed in the context of their acquaintance.